Botanical Exploration and Crater Vegetation Survey of Mt. Galunggung, West Java - Musyarofah Zuhri; Harry Wiriadinata; Ratna Suti Astuti; Supan Hadiwaluyo; Syamsudin Syamsudin (Journal of Tropical Life Science, 2016)
Botanical exploration at Mt. Galunggung protected forest, West Java was conducted in June 2014. This study was aimed to collect plant living specimen for ex-situ conservation purpose of Kuningan Botanic Garden and to conduct vegetation analysis in crater area. Random inventory method at 600-1200 m asl was used to collect plant in that area. Vegetation analysis of tree, shrub and herb were used line transect methods. Result showed that 273 collection numbers of plant living species were collected from Mt. Galunggung, which consisted of 213 species, 143 genus and 72 families. Plant families which most collected were Moraceae, Euphorbiaceae, Arecaceae and Lauraceae respectively. In crater area was collected a lot of pioneer plant, such as dawola (Trema cannabina Lour.), paku tiang (Cyathea spp.), nangsi (Villebrunea rubescens (Blume) Blume), muncang cina (Ostodes paniculata Blume), mara (Macaranga tanarius (L.) Mull.Arg.), and kareumbi (Homalanthus populneus (Geiseler) Pax). Furthermore, in secondary remnant forest were collected typical plants of Java mountains such as saninten (Castanopsis argentea (Blume) A.DC., puspa (Schima wallichii Choisy) and some of tree seedlings from Lauraceae family. Vegetation affected by eruption in Mt. Galunggung is in early stage of forest succession and still develops to next stage of succession. Tree, shrub and herb in the crater area were dominated by Cyathea contaminans (Wall. Ex Hook.) Copel., Calliandra callothyrsus Meisn. and Ageratina riparia (Regel) R.M.King & H.Rob. with H’ was 0.35, 0.31 and 0.30 respectively.